Application of SAP and PEG as curing agents for ordinary cement-based systems: impact on the early age properties of paste and mortar with water-to-cement ratio of 0.4 and above. Issue 10 (3rd October 2017) - Sarbapalli, Dipobrato; Dhabalia, Yash; Sarkar, Kaustav; Bhattacharjee, Bishwajit
Abstract : The feasibility of utilising "Superabsorbent Polymer (SAP)" and "Polyethylene glycol (PEG)" as curing agents for ordinary cement-based systems with water-to-cement ratio of .4 and above has been investigated. The investigation considers water-to-cement ratios of .4, .5 and .6 and curing ages of 3, 7 and 28 days. A commercially available SAP of 300 μm average particle size and a laboratory grade PEG with an average molecular mass of 6000 have been used as curing agents. The impact of SAP and PEG dosages on consistency, setting time and degree of hydration of paste samples has been evaluated. The evolution of strength, water absorption and water retention characteristics has been studied using mortar samples and compared with respect to water- and air-cured control. SAP doses in the range of .3–1.0% of cement mass have been found to be effective over the full range of water-to-cement ratio tested. PEG admixed at the rate of .5–2.0% has been found to be beneficial at .50% dose for water-to-cement ratio of .4, thus indicating its suitability for low water-to-cement ratio systems. Observations of this preliminary study indicate the viability of implementing SAP and PEG as self-curing agents albeit with certain limitations requiring further investigation.